Small and Marginal Farmers - Vulnerable to flimsy Agricultural framework - Manik, , Bibhu Kaibalya (International Journal of Psychosocial Rehabilitation, 2020)
Unenthusiastic inclination in policy implementation and need-based developmental intervention in the agro-sector has sketched out its significance in 2018 States election in India. The evolving environment of global economic order influenced by the Liberalization of Trade, in addition, has posited the challenges about the requirement of more balanced approach in the legal framework of the country especially, for the agricultural sector. The agro-policy issues require discrete focus upon wide range of stakes of agricultural community, environmental, rural, and agribusiness communities of the country for shaping and augmenting: a) effective structural relationships with institutional framework and legal foundations relating to the stakeholders involved in production and marketing system to ensure better production operations to meet the sustaining food security of the country and global competition; b) visionary attempt to ensure adopting of environmental-friendly new technologies for the agro-production as well as scientific assurances considering consumers’ concerns regarding food safety; c) renewed attention in the safety nets concerted in the legal frameworks relating to private sector risk management strategies, agricultural production, market-incentives, environmental amenities, public interest and private rights, etc.